2017
DOI: 10.1021/acs.jpcc.7b05761
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Operational Stability of Phosphorescent OLED Host Molecules from First Principles: A Case Study

Abstract: Low operational stability is the main limiting factor for commercialization of the blue phosphorescent organic light emitting diodes (PhOLEDs). The high energy and long lifetime of triplet excitons in blue PhOLEDs makes them more prone to degradation. Degradation of the host molecules in the emitting layer of PhOLEDs is one of the possible mechanisms leading to the luminosity loss in the course of device operation. Although possible degradation mechanisms are proposed in the literature, predicting the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 70 publications
0
37
0
Order By: Relevance
“…Facial/meridional stereoisomerism in trisbidentate Ir(III) complexes strongly determines their photophysical properties and thereby their efficiency and stability within a phosphorescence-based organic light-emitting diode (PhOLED) device. [9] In recent years, numerous computational [10][11][12] and experimental [13][14][15][16] efforts have been made to decipher the underlying degradation mechanisms, and still many open questions remain. These investigations highlight the protagonistic role of a non-previously described 3 MC (triplet metal-centred) state bearing one stretched trans Ir-N position.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Facial/meridional stereoisomerism in trisbidentate Ir(III) complexes strongly determines their photophysical properties and thereby their efficiency and stability within a phosphorescence-based organic light-emitting diode (PhOLED) device. [9] In recent years, numerous computational [10][11][12] and experimental [13][14][15][16] efforts have been made to decipher the underlying degradation mechanisms, and still many open questions remain. These investigations highlight the protagonistic role of a non-previously described 3 MC (triplet metal-centred) state bearing one stretched trans Ir-N position.…”
mentioning
confidence: 99%
“…[1,2] To further improve their device operational lifetimes, and especially in the case of blue phosphors, it is crucial to acquire durable and efficient materials that do not suffer intrinsic chemical degradation upon PhOLED operation. [9] In recent years, numerous computational [10][11][12] and experimental [13][14][15][16] efforts have been made to decipher the underlying degradation mechanisms, and still many open questions remain. [9] In recent years, numerous computational [10][11][12] and experimental [13][14][15][16] efforts have been made to decipher the underlying degradation mechanisms, and still many open questions remain.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that susceptible weak chemical bonds and their possible fragments could be theoretical simulated via identification of dissociated activation energy (E A ) under time dependent density functional theory (TDDFT) calculations. [17][18][19][20] However, the actual relationship between Organic light-emitting diodes (OLEDs) employing exciplex cohosts have gained attractive interest due to the promising high efficiency, low driving voltage, and potential low cost in future solid-state lighting sources and full-color displays. However, their device lifetime is still the most challenging weakness and rarely studied, which is regarded as a time consuming and complicated work.…”
Section: Doi: 101002/advs201802246mentioning
confidence: 99%
“…As charged-excited state is extremely short-lived and difficult to measure clearly, however, their formative probabilities show positive dependence to the polaron and exciton density. [19] Fortunately, the amount of polarons could be properly controlled by optimizing HTM:ETM ratios. [34] Thus, we mainly discuss coordinated relationship between average exciton lifetime (<τ>) and ΔE EPA here.…”
Section: Light-emitting Diodesmentioning
confidence: 99%
See 1 more Smart Citation